2014
DOI: 10.1523/jneurosci.5002-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration by Activation of the Microglial Complement-Phagosome Pathway

Abstract: Systemic inflammatory reactions have been postulated to exacerbate neurodegenerative diseases via microglial activation. We now demonstrate in vivo that repeated systemic challenge of mice over four consecutive days with bacterial LPS maintained an elevated microglial inflammatory phenotype and induced loss of dopaminergic neurons in the substantia nigra. The same total cumulative LPS dose given within a single application did not induce neurodegeneration. Whole-genome transcriptome analysis of the brain demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
176
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(191 citation statements)
references
References 47 publications
13
176
0
2
Order By: Relevance
“…The induction of a chronic inflammatory state by repeated LPS injections may be a more reliable method to test the effects of environmental changes, such as changes in diet or ambient temperature, e.g, on immune responses of pigs (67). This assumption is supported by a recent study that found that, compared with a single LPS injection, repeated injections of LPS resulted in higher brain proinflammatory cytokine responses in rats (68).…”
Section: Discussionmentioning
confidence: 94%
“…The induction of a chronic inflammatory state by repeated LPS injections may be a more reliable method to test the effects of environmental changes, such as changes in diet or ambient temperature, e.g, on immune responses of pigs (67). This assumption is supported by a recent study that found that, compared with a single LPS injection, repeated injections of LPS resulted in higher brain proinflammatory cytokine responses in rats (68).…”
Section: Discussionmentioning
confidence: 94%
“…They comprise cytokines (Buffo et al 2010;Falsig et al 2004a;Garwood et al 2011); lipocalin 2 (Bi et al 2013), components of the complement system (Bodea et al 2014;Pekny et al 2007), or changes due to altered ATPase expression (Gallardo et al 2014). Besides these mostly proteinaceaous molecules, also some small molecules with cell death-inducing properties have been described.…”
Section: Discussionmentioning
confidence: 99%
“…It has been corroborated that microglia can be primed toward a pro-inflammatory state by the C3 receptor [85]. An in vivo study that continually induced a microglial inflammatory phenotype in mice, using lipopolysaccharide (LPS), showed an activation of the microglial complement-phagosome pathway that subsequently induced neurodegeneration [86]. …”
Section: Microglia and Neuroinflammation: Beneficial And Detrimentmentioning
confidence: 99%